Transient C5 Sensory and Motor Blockade After a Unilateral T4 Paravertebral Block: A Case Report. Issue 4 (12th April 2022) - Mortazavi, Siavash; Trinder, Matthew; Li, Ran; Hennessy, Brien; Yeo, Allen
Abstract : A thoracic paravertebral block (TPVB) can provide anesthesia for breast cancer surgeries. This case report describes a 58-year-old woman with a prolonged ipsilateral dense C5 dermatomal sensory and motor blockade after receiving a TPVB at T4 with 40 mL of 0.2% ropivacaine for a left total mastectomy, suggesting a high cephalad spread of anesthesia up to C5 paravertebral spaces. The lower extremities and the diaphragm were not involved. It is possible that the large volume of local anesthetic, even at low concentration, combined with her previous neural pathology and surgical laminectomy resulted in unexpected postoperative neurological changes.